Transcription factors and CD4 T cells seeking identity: masters, minions, setters and spikers. Issue 3 (13th June 2013) - Vahedi, Golnaz; Kanno, Yuka; Sartorelli, Vittorio; O'Shea, John J.
Summary Naive T cells differentiate and become distinct subsets in response to changes in the cytokine milieu. Such specialization arises through a complex and dynamic utilization of cis‐regulatory enhancer elements. In this brief essay, we review recent findings on the relative contributions of sensors of the cytokine milieu, especially the signal transducer and activator of transcription family transcription factors, 'master regulators', and other transcription factors in the enhancer architecture of T cells. These findings provide new insights into how signal transduction impinges upon the genome.